Model pendidikan profesi guru (PPG) vokasi - Mustika Nuramalia Handayani; As’ari Djohar (Inovasi Kurikulum, 2020)
Teachers at every level of education must have a professional educator certificate obtained through professional education as well as vocational high school (SMK) teachers. The provision of professional vocational teachers is one of the special tasks in the revitalization of vocational schools. Vocational Teacher Professional Education (PPGV) is expected to produce professional teachers to educate a superior and competitive generation. The PPGV model in Indonesia currently uses concurrent and consecutive models. PPGV In Position uses a concurrent model where the curriculum contains scientific fields of study and education. Pre-Service PPGV uses a consecutive model in which the curriculum contains educational science, while the field of study has been previously studied in undergraduate education by the majority of Pre-Service PPG participants who are dominated by non-educational scholars.   Abstrak Guru di setiap jenjang pendidikan harus memiliki sertifikat profesi pendidik yang diperoleh melalui pendidikan profesi begitu pun dengan guru Sekolah Menengah Kejuruan (SMK). Penyediaan guru SMK profesional merupakan salah satu tugas khusus dalam revitalisasi SMK. Pendidikan Profesi Guru Vokasi (PPGV) diharapkan dapat menghasilkan guru-guru profesional untuk mendidik generasi unggul dan kompetitif. Model PPGV di Indonesia saat ini menggunakan model konkuren dan konsekutif. PPGV Dalam Jabatan menggunakan model konkuren di mana dalam kurikulumnya memuat keilmuan bidang studi dan pendidikan. PPGV Pra Jabatan menggunakan model konsekutif di mana dalam kurikulumnya memuat keilmuan pendidikan, sedangkan keilmuan bidang studi telah dipelajari sebelumnya pada pendidikan sarjana oleh mayoritas peserta PPG Pra Jabatan yang didominasi oleh sarjana nonpendidikan. Kata kunci: Model Pendidikan Profesi Guru; Konkuren; Konsekutif